γδ T Cells Participating in Nervous Systems: A Story of Jekyll and Hyde - Li, Yunxuan; Zhang, Yixi; Zeng, Xun (Frontiers in Immunology, 2021)
γδ T cells are distributed in various lymphoid and nonlymphoid tissues, and act as early responders in many conditions. Previous studies have proven their significant roles in infection, cancer, autoimmune diseases and tissue maintenance. Recently, accumulating researches have highlighted the crosstalk between γδ T cells and nervous systems. In these reports, γδ T cells maintain some physiological functions of central nervous system by secreting interleukin (IL) 17, and neurons like nociceptors can in turn regulate the activity of γδ T cells. Moreover, γδ T cells are involved in neuroinflammation such as stroke and multiple sclerosis. This review illustrates the relationship between γδ T cells and nervous systems in physiological and pathological conditions.